An evaluation of factors that influence children's instruction following. Issue 1 (11th October 2013) - Sy, Jolene R.; Donaldson, Jeanne M.; Vollmer, Timothy R.; Pizarro, Eliana
<x xml:space="preserve">Abstract</x> Behavior that resembles instruction following might sometimes be under stimulus control of extraneous variables. We evaluated the effects of some of these variables (i.e., presence of relevant objects, associations between instructions and object sets) with 3 children with intellectual disabilities. In Experiment 1, we assessed whether subjects were more likely to follow instructions that required object manipulation and whether subjects were more likely to follow these instructions when only relevant objects were present. All subjects were more likely to follow instructions that required object manipulation when only relevant objects were present. In Experiment 2, we evaluated whether instruction following would be less likely if the same object set was associated with multiple instructions, and found this to be the case for 2 of 2 subjects. Findings highlight the need to train instruction following under different conditions to ensure that responding comes under stimulus control of the instructions.